(untitled) - Madlenak, Radovan; Zboranova, Alzbeta (Doprava a spoje, 2007)
The Internet is nowadays a widely accepted medium which enables millions of people all over the world to communicate every day. For a few years now, the Internet has been regarded by many people as a fascinating instrument for marketing purposes through which thousands of people in the target group can be addressed. This article deals with basic aspects of e-marketing, finding of suitable tools for e-marketing and recommendations for successful e-marketing.